Effectiveness of Project Based Learning (PjBL) Model on Mathematics Learning Outcomes of Elementary School Students - Fitria Wulandari; Uswatin Anggraeni; Ria Anggraeni Puspitasari; Voni Andriyani; Syihabudin Robbani (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study analyzes the effectiveness of the Project-Based Learning (PjBL) model on primary school students' mathematics learning outcomes. The research highlights the importance of primary education in developing students' cognitive and analytical skills, addressing challenges such as low interest in mathematics. Using a quantitative design, 24 students were randomly sampled. Data were collected through pretests and posttests to measure students' mathematics learning outcomes before and after implementing the PjBL model. Descriptive statistics were employed to calculate the mean, standard deviation, and standard error. A paired samples t-test was conducted to compare pretest and posttest scores, revealing a significant improvement in learning outcomes (mean difference = -11.125, p < 0.05). The findings confirm that the PjBL model significantly enhances mathematics learning outcomes. This study concludes that the PjBL model is an effective instructional strategy to improve mathematics achievement in primary education.